BIOACTIVE COMPOUNDS OF SPONGE FOR AQUACULTURE AND POTENTIAL METHODS FOR SPONGE CULTIVATION - Ruzkiah Asaf; Andi Nur Samsi; Admi Athirah; Mudian Paena (Jurnal Natural, 2018)
Aquaculture is an important sector for Indonesian economic, however, the spreads of diseases during farming remains a problem in developing Indonesian aquaculture. The sponge is known as the source of potential bioactive to combat pathogenic diseases in aquaculture.  However, the intensifying exploitation of wild sponge tends to the depreses population of sponges in nature. This article reviews bioactive originating from sponges and potential methods in developing sponges cultivations under in-situ and ex-situ methodologies.